DETERMINATION OF THE MOST INFORMATIVE IMMUNOHISTOCHEMICALMARKERS OF ENDOMETRIAL HYPERPLASIA FOR THE CHOICE OF TREATMENT STRATEGY IN WOMEN OF REPRODUCTIVE AGE - Хасхачих, Дмитрий; Кукина, Галина; Гапонова, Елена; Потапов, Валентин (SWorldJournal, 2021)
Тhe article considers the most informative immunohistochemical markers of endometrial hyperplasia (GE) without atypia, which should improve diagnostic methods for prescribing therapy. Such markers, according to many studies, may include an increase in th